Korelasi Model Pembelajaran Student Team Achievement Division (STAD) Terhadap Hasil Belajar Siswa Pada Materi Konsep Asam Basa - Fladi Rivera Kalubota; Dokri Gumolung; Joice D. S. Caroles (Oxygenius Journal Of Chemistry Education, 2022)
This study aims to determine how much the correlation value in the use of the learning model Studen Team Achievement Division (STAD) on student learning outcomes. The steps of the STAD learning model, namely: 1) convey learning objectives and motivate students, 2) organize students into study group consisting of 4-6 people, 3) convey information, 4) guide groups to work and study, 5) elevate students learning outcomes, 6) to give appreciation. This research wash conducted at SMA Negeri 5 Halmahera Utara in the even semester of the 2019-2020 school year. The sample used was 20 students of class XI-MIPA 1. Data collection technique using students attitude questionnaires and posttest questions. The results of the study a correlation coefficient value of 0.731, the value of the determinant coefficient of 53.44%. Score tcount > ttable (4.537 > 1.73406) so that there is a significant influence between the STAD learning model and student learning outcomes on the acid-base concept material.